Identifying Impressive Landscape Objects Based on Geotagged Photographs (A Case Study of Self-Portraits and Ordinary Photos) - Hadi, Akhmad Arifin; Mizuuchi, Yusuke; Honjo, Tsuyoshi; Furuya, Katsunori (Journal of Indonesian Tourism and Development Studies, 2017)
Photographs are important elements in ecotourism activities. The current research utilizes respondents' geotagged photographs to explore the potential landscape objects with its locations. The study invited 61 respondents to come to Bukit Kucing Forest and capture impressive landscape objects. The study used Getis-Org Gi* Hotspot analysis tools in ArcGIS to identify hotspots places based on the numbers of closest photos captured points to five-meters trail segments. There were 1,712 geo-tagged photographs consist of 412 self-portraits and 1,300 ordinary photographs collected from respondents. The finding shows that geotagged photographs, both self-portraits and ordinary photographs, performed hotspots places that containedimpressive landscape objects including: physical structures, wide opening area and panoramic views. Self-portraits' hotspots which were detected more spread and less number than ordinary photographs were able to perform places that werenot detected in ordinary photographs' hotspots. The current work shows that geotagged self-portraits is able to be utilized as object research in identifying hotspots of impressive landscape spaces and objects. The maps of geotagged photographs both ordinary photographs and self-portraits are able to be used as information of visitors' preferences for developing masterplan of ecotourism. Keywords: forest, Geotagged, hotspots, photographs, self-portraits.